2015
DOI: 10.1371/journal.pone.0121408
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes of the Middle Hepatic Vein in Patients with Pulmonary Hypertension Using Echocardiography

Abstract: The aim of this study was to analyze the changes of the middle hepatic vein (MHV) spectra in patients with pulmonary hypertension (PH) caused by congenital heart disease (CHD) and determine the proper parameters of MHV to predict PH. Eighty patients with CHD were included, whose pulmonary artery pressure was measured via right heart catheterization, and the MHV spectra were detected via echocardiography. The peak value of velocity (V) and velocity time integral (VTI) of the waves, including S wave, D wave and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…In their study, they only analyzed the normal basic waveform of hepatic vein, including two antegrade waves ( S wave and D wave) and one retrograde (A wave). 8 In this study, 19 patients showed normal four phagic waves in hepatic venous duplex where deep S in between small A wave and small V wave and that patients have mild pulmonary hypertension. In 38 moderate PH patients, S wave became very small in between large A wave and small V wave are seen.…”
Section: Discussionmentioning
confidence: 54%
“…In their study, they only analyzed the normal basic waveform of hepatic vein, including two antegrade waves ( S wave and D wave) and one retrograde (A wave). 8 In this study, 19 patients showed normal four phagic waves in hepatic venous duplex where deep S in between small A wave and small V wave and that patients have mild pulmonary hypertension. In 38 moderate PH patients, S wave became very small in between large A wave and small V wave are seen.…”
Section: Discussionmentioning
confidence: 54%
“…19 In addition, the lengthening of isovolumic relaxation due to TR, which often accompanies APE, would lead to increased pressure and volume in the RA during the early rapid emptying phase. 20 This lowers the venous return and also decreases D wave velocity. Acutely developing pulmonary hypertension in APE can also further diminish D wave.…”
Section: Discussionmentioning
confidence: 99%
“…In APE, RV relaxation is worsened with RVD . In addition, the lengthening of isovolumic relaxation due to TR, which often accompanies APE, would lead to increased pressure and volume in the RA during the early rapid emptying phase . This lowers the venous return and also decreases D wave velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Normal atrial reversal velocity should be inferior to 50% of the systolic hepatic venous velocity ( 45 ). Higher atrial reversal peak hepatic venous Doppler velocities values have been reported in cases of elevated right atrial pressure ( 46 ), RV diastolic dysfunction ( 47 , 48 ), pulmonic stenosis ( 49 ), and pulmonary hypertension ( 50 – 52 ), regardless of underlying mechanism ( 53 ). Because the hepatic venous Doppler velocity correlates with the CFV Doppler velocity, we elected to apply the same criteria (> 50%) to identify an abnormal reversed CFV Doppler waveform peak velocity.…”
Section: Discussionmentioning
confidence: 99%